Parameters design optimization of grading ring based on electric field analysis through response surface methodology - Ahsan, Matiullah; Baharom, Md Nor Ramdon; Zainal, Zainab; Khalil, Ihsan Ullah (elsevier, 2024)
This research delves into the primary cause of the ageing of insulated cross-arms in the field, which is attributed to the high electric stress experienced at the end fittings. To address this issue, a novel technique is introduced to meticulously analyse the influence of Grading rings on the electric field (E-field) stress, with the goal of regulating it within the prescribed limits on the surface of the insulated cross-arm. By employing advanced methodologies such as finite element analysis and design of experiment approaches, the impact of various geometrical characteristics of Grading rings on the E-field is comprehensively investigated. Through the application of the analysis of variance, the primary and interaction effects of these factors are carefully examined. Additionally, leveraging the power of the response surface technique, an optimal link between the E-field and the geometrical parameters is modelled and optimized. The results of this comprehensive study unequivocally reveal the profound influence of the geometrical parameters of Grading rings on the E-field. Furthermore, diligent efforts are made to estimate the Grading ring parameters that will effectively regulate the E-field within the suggested maximum threshold based on the derived model. The proposed technique not only significantly reduces the computational analysis time but also serves as an efficient and invaluable tool for investigating the intricate geometry of Grading rings without imposing any additional computing burden. According to the findings, the E-field is most impacted by the factors H, D, and T to optimise the shape of grading rings used in insulated cross-arms. The main objective was achieved by reducing the maximum E-field value by 65% compared to the E-field without a grading ring, which has been accomplished. The suggested technique provides a quick and easy way to analyse and improve the intricate geometry of grading rings. As a result, it lowers the cost and time related to computational analysis without needing an excessive amount of computing work to do this.